KEADILAN DAN KESADARAN “AKU” DAN “LIYAN” DALAM PENEGAKAN HUKUM KASUS TINDAK PIDANA KORUPSI DI INDONESIA: Tinjauan Relasionalitas - F.X. Armada Riyanto - Sinaga, Andreas Marison; Riyanto, F.X. Armada; Marianta, Yohanes I Wayan (Sanjiwani: Jurnal Filsafat, 2023)
This paper talks about the awareness of "I" and "Other" in law enforcement cases of corruption in Indonesia. This paper aims to analyze how awareness of "I" and "Other" in cases of law enforcement on corruption in Indonesia is considered to be fading which has an impact on attitudes of justice for both subjects. Corruption is a criminal act carried out by a handful or a group of people to enrich themselves by utilizing the means they have, such as position and power. The method used in this paper is qualitative research by means of a literature study sourced from the Relationality book coupled with the literature that supports the discussion of this paper. The results found in this paper are that law enforcement on corruption in Indonesia is considered weak and powerless. This is because human resources are not aware of the true meaning of "I-ness" so it makes other people or "Others" suffer. Lack of understanding about awareness of "I", in cases of law enforcement on corruption in Indonesia is the main reason why "Others" get discriminated against and injustice in their lives.